Beispiel Nr: 02
$ \text{Gegeben: } \\ p_1: y=a_1x^{2}+b_1x+c_1 \qquad p_2: y=a_2x^{2}+b_2x+c_2\\ \text{Gesucht:Schnittpunkte zwischen 2 Parabeln} \\ \text{Parabel-Parabel}\\ \textbf{Gegeben:} \\ p_1: y= x^2+2 \qquad p_2: y=-\frac{1}{2}x^2+x+1\frac{1}{2} \\ \\ \textbf{Rechnung:} \\f\left(x\right)= x^2+2\qquad g\left(x\right)=-\frac{1}{2}x^2+x+1\frac{1}{2}\\ \bullet \text{Schnittpunkte zwischen zwei Funktionen} \\ f\left(x\right)=g\left(x\right) \\ x^2+2=-\frac{1}{2}x^2+x+1\frac{1}{2} \\ x^2+2-(-\frac{1}{2}x^2+x+1\frac{1}{2})=0\\ \begin{array}{l|l|l} \begin{array}{l} \text{a-b-c Formel}\\ \hline 1\frac{1}{2}x^{2}-1x+\frac{1}{2} =0\\ x_{1/2}=\displaystyle\frac{+1 \pm\sqrt{\left(-1\right)^{2}-4 \cdot 1\frac{1}{2} \cdot \frac{1}{2}}}{2\cdot1\frac{1}{2}}\\ x_{1/2}=\displaystyle \frac{+1 \pm\sqrt{-2}}{3}\\ \text{Diskriminante negativ keine Lösung} \end{array}& \begin{array}{l} \text{p-q Formel}\\ \hline \\ 1\frac{1}{2}x^{2}-1x+\frac{1}{2} =0 \qquad /:1\frac{1}{2} \\ x^{2}-\frac{2}{3}x+\frac{1}{3} =0 \\ x_{1/2}=\displaystyle -\frac{-\frac{2}{3}}{2}\pm\sqrt{\left(\frac{\left(-\frac{2}{3}\right)}{2}\right)^2-\frac{1}{3}} \\ x_{1/2}=\displaystyle \frac{1}{3}\pm\sqrt{-\frac{2}{9}} \\ \text{Diskriminante negativ keine Lösung} \end{array}\\ \end{array}\\ $